Definition and criteria of classification of consumer legal status: theoretical and legal research - Старицька, О. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the author examines the concept and features of the legal status of the consumer,given the different classification criteria of its rights and obligations.